Cranial nerve palsies after shunting of an isolated fourth ventricle. (9th September 2015) - Simonin, Alexandre; Levivier, Marc; Bloch, Jocelyne; Messerer, Mahmoud
Abstract : An isolated fourth ventricle is characterised by cerebrospinal fluid (CSF) trapping in the fourth ventricle. Although there is no consensus regarding treatment, ventriculoperitoneal (VP) shunting of the fourth ventricle is an option. Complications include infection, mechanical irritation of the brainstem, malfunction and overdrainage. Cranial nerve palsy is a rare complication and has been mostly described in children. We present two adult cases of abducens and facial nerve palsies occurring secondary to this procedure. Placement of a higher resistance valve brought about complete recovery in one patient while withdrawal of the catheter by a few millimetres led to complete recovery in the second patient.